Can you afford to be ill : hospital service plan (London : The London Association for Hospital Services Limited)
1945 1945 1940s 15 pages : illustrations homes, including the cost of medical and surgical fees in connection with the treatment received, provided this treatment has been recommended by a registered medical practitioner. The voluntary hospitals and the British Medical Association are anxious to establish a comprehensive contributory plan which will entirely relieve people of moderate means from the payment of hospital charges and medical fee. This plan is being pursued now as far as present circumstances allow, and arrangements have already been made with certain hospitals (details are obtainable from the Secretary) for a comprehensive plan to operate now. It is hoped that these facilities can be more widely extended when the conditions imposed by the war on the hospitals and medical profession are relaxed. There are, of course, certain expenses connected with medical treatment in respect of which the Hospital Service Plan is, at this stage, unable to render assistance, as the schedule of benefits must naturally harmonise with the rates of contribution in order to maintain the solvency of the scheme, and it is desirable to keep contributions within reasonable limits. These necessary limitations will be found on page 8. 4 292/842/2/63